Optimalisasi Pembelajaran Virtual Melalui Workshop Penggunaan Aplikasi Microsoft Teams di SMP Unismuh Makassar dan SMA Unismuh Makassar - Sitti Rahmah Tahir; St Nur Humairah Halim; Randy Saputra Mahmud; Sri Satriani (Rengganis Jurnal Pengabdian Masyarakat, 2021)
This workshop on using the Microsoft teams application aims to help teachers at school Unismuh Junior High School in Makassar and Unismuh Senior High School in Makassar can further optimize learning virtual during the pandemic and after the pandemic, so that not only the professional competence of teachers in the IT field can increase but can also motivate students to be more motivated to improve their learning achievements, in addition to the features of Microsoft teams, project-based learning during this period pandemic and after the pandemic can be done more interactively. The method used in this implementation is training as well as mentoring, where the steps taken are (1) providing material about Microsoft development and introduction to Microsoft teams features using lecture and quiz methods, (2) training on the use of Microsoft teams in providing learning materials and assignments to students, and (3) mentoring and discussions with resource persons about the use of Microsoft Teams in the subjects taught by each teacher.